2019
DOI: 10.1007/s00421-019-04074-0
|View full text |Cite
|
Sign up to set email alerts
|

The cTnT response to acute exercise at the onset of an endurance training program: evidence of exercise preconditioning?

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…a marker of myocardial injury, found after strenuous exercise. Recent work revealed that a single session of endurance exercise is protective against the exercise-induced rise in cardiac troponin T. In two other studies from separate laboratories, it was shown that cTnT was blunted during a second exercise session that was separated by both 4 and 48 h of recovery in previously inactive, young women (Nie et al 2019;Zhang et al 2019). These findings, although indirectly, provide some support for the concept that SEP leads to smaller tissue injury.…”
Section: Does Sep Also Prevent Cardiac and Vascular Injury In Humans?mentioning
confidence: 84%
See 1 more Smart Citation
“…a marker of myocardial injury, found after strenuous exercise. Recent work revealed that a single session of endurance exercise is protective against the exercise-induced rise in cardiac troponin T. In two other studies from separate laboratories, it was shown that cTnT was blunted during a second exercise session that was separated by both 4 and 48 h of recovery in previously inactive, young women (Nie et al 2019;Zhang et al 2019). These findings, although indirectly, provide some support for the concept that SEP leads to smaller tissue injury.…”
Section: Does Sep Also Prevent Cardiac and Vascular Injury In Humans?mentioning
confidence: 84%
“…2019; Zhang et al . 2019). These findings, although indirectly, provide some support for the concept that SEP leads to smaller tissue injury.…”
Section: Does Sep Also Prevent Cardiac and Vascular Injury In Humans?mentioning
confidence: 99%
“…VO 2max was determined using a graded cycling exercise protocol that has been described previously. 5,11 The participants began at 50 W with a pedal frequency of 60 rpm on a cycle ergometer (Monark, 839E, Sweden); power output was increased by 20 W every 3 min until volitional exhaustion. Volitional exhaustion was defined as the point at which the subject could no longer maintain the required exercise intensity.…”
Section: Methodsmentioning
confidence: 99%
“…For example, a single bout of exercise preceding cardiac ischaemiareperfusion injury affords protection, leading to a smaller infarct size in animal models (8). Interestingly, exercise-induced cTnI release was blunted during a second exercise session timed 48-hours later (9) or following training (10), and declined with successive days of running in humans (11). Whilst these findings support the ability of exercise to attenuate exercise-induced cTnI release, no studies evaluated these effects in groups with elevated risk.…”
Section: Introductionmentioning
confidence: 99%